Strategic Pathways for MSME Development Through Business Legality and Halal Certification: Evidence from Ambon City - Fadly Usman; Djufri R Pattilouw; Hendri D Hahury (LP2M IAIN Palopo, 2026)
This study examines the internal and external factors influencing the development of Micro, Small, and Medium Enterprises (MSMEs) in Ambon City, with particular attention to business legality through the Business Identification Number (Nomor Induk Berusaha, NIB) and halal product certification. A qualitative, descriptive-analytical approach was employed, drawing on in-depth interviews, observations, and document analysis involving 20 informants comprising MSME actors and relevant stakeholders. The findings indicate that internal motivation, awareness of legal compliance, and commitment to halal principles constitute key strengths. In contrast, limited access to capital, low administrative literacy, and reliance on external facilitators emerge as significant internal constraints. Externally, free NIB registration and halal certification programs, mentoring initiatives, and improved access to financing and markets present substantial opportunities. However, these opportunities are tempered by challenges such as limited availability of halal raw materials and technical barriers associated with digital systems. A weighted SWOT analysis (Internal Factor Analysis Summary, IFAS and External Factor Analysis Summary, EFAS) identifies four strategic directions: (1) accelerating business legality and halal certification (S-O); (2) strengthening internal capacity through integrated mentoring (W-O); (3) mitigating external threats through internal discipline and regulatory adaptation (S-T); and (4) adopting defensive strategies based on business scale adjustment (W-T). The study concludes that integrating NIB registration with halal certification can enhance MSME competitiveness, expand market access, and support long-term sustainability in Ambon City.